Levantamento dos procedimentos de recuperações em elementos de fundações por problemas de reação álcali agregado: estudos de casos. - Silva, Cristiane Santana da (2019)
The Aggregate Alkali Reaction (RAA), a chemical reaction that occurs between alkalis, usually coming from cement and the reactive aggregate, which in the presence of water expands causing a progressive deterioration in the concrete element which may lead to its loss of stability. This reaction is well known in the technical field and in the Metropolitan Region of Recife (RMR), with several cases of foundations that were reached and recovered. Thus, it was observed the importance and necessity to carry out a survey in the recovery procedures in elements of the foundations due to Reaction problems, including the case studies in fifty rehabilitated foundations. A semi-structured questionnaire with seventeen questions was applied methodologically to draw a profile of the recovery processes used in the foundations of buildings affected by the RAA, as well as to consult and analyze the technical collection of some supervisory companies or performers of recoveries in the foundations of. RMR buildings. These results allowed us to draw a profile of the foundations, establishing the similarities of the foundations affected and determining influencing factors. Also knowing the advances about the materials and processes applied in the recovery of the elements and the conditioning factors for the use of the containment reinforcement. Also found were foundations that, after being restored, left an inspection window for further verification. This detail is extremely important for the monitoring of these foundations.